Understanding Material Flow at the Interface of Friction Stir Lap Welding (FSLW) of Al-to-Cu Plates - Parningotan, Doddy (Auckland University of Technology, 2019)
Aluminium to copper bimetal parts have seen wide use in electrical componentry. A continuous interface between the two alloys is necessary in order to have unhampered electron path. Friction stir welding, especially in a lap configuration (FSLW), is a proven method in the production of continuous welds with dissimilar metals, producing a metallurgical joint in the form of interfacial intermetallic layer formed in between the plates. However, from existing literature there is no evidence of a discontinuity-free interface in aluminium-to-copper FSLW.
Keywords: Friction stir lap welding; Aluminium-to-copper; Interfacial continuity; Material flow; Scriber